2019
DOI: 10.1111/1759-7714.13107
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of the preoperative albumin to alkaline phosphatase ratio in patients with non‐small cell lung cancer after surgery

Abstract: Background To assess the potential prognostic value of the albumin to alkaline phosphatase ratio (AAPR) in patients with non‐small cell lung cancer (NSCLC) after surgery. Methods The log‐rank and Kaplan‐Meier analyses were performed to detect differences in survival levels between different groups. A model of Cox proportional hazards was used to perform univariate and multivariate survival analyses. Comparisons of receiver operating characteristic (ROC) curves and the likelihood ratio test (LRT) were also util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Malnutrition can lead to the decline of immune function in cancer patients, thus increasing the risk of postoperative complications and tumor progression. 21 Previous studies have reported that hypoalbuminemia is associated with disease progression and poor prognosis in patients with colon cancer, 22 pancreatic cancer, 23 non-small cell lung cancer, 24 ovarian cancer, 25 and GC. 26 Furthermore, this study shows that preoperative CEA is an independent prognostic factor of survival, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition can lead to the decline of immune function in cancer patients, thus increasing the risk of postoperative complications and tumor progression. 21 Previous studies have reported that hypoalbuminemia is associated with disease progression and poor prognosis in patients with colon cancer, 22 pancreatic cancer, 23 non-small cell lung cancer, 24 ovarian cancer, 25 and GC. 26 Furthermore, this study shows that preoperative CEA is an independent prognostic factor of survival, consistent with previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the included studies were shown in Table 1. In the current research, 15 retrospective articles with 6,062 cancer patients were included [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Because of the subgroup analysis in three articles [15,17,19], we regarded them as 2 or 3 independent studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…[5][6][7][8][9] The albumin-to-alkaline phosphatase ratio (AAPR), a novel blood biomarker, has been shown to be associated with the prognosis of liver cancer, nasopharyngeal cancer, small cell lung cancer, kidney cancer and other tumors. [10][11][12][13] However, data on the relationship between AAPR and bladder tumors are rare. The aim of this study was to investigate the relationship between preoperative AAPR and the overall survival of patients undergoing radical cystectomy of MIBC.…”
Section: Introductionmentioning
confidence: 99%